Entering out-of-home care during childhood: Cumulative incidence study in Canada and Australia. (September 2016) - O'Donnell, Melissa; Maclean, Miriam; Sims, Scott; Brownell, Marni; Ekuma, Okechukwu; Gilbert, Ruth
Abstract: Cumulative incidence provides a more accurate indicator than annual incidence rates of the number of children who experience out-of-home care during childhood. The study utilises a cohort of all children born in Western Australia (WA) 1994–2005 and Manitoba 1998–2008 using de-identified linked data. Life tables were used to calculate the age-specific cumulative incidence over time and for at-risk groups. Cox regression was used to compare risk factors for entry to care. Manitoba had a larger proportion of children entering care compared to WA (9.4% vs 1.5% by age 12). Over time children entered care at a younger age in both WA (HR = 1.5, CI:1.4–1.5) and Manitoba (HR = 1.5, CI:1.5–1.6). Similar factors were associated with earlier age care entries in both countries including: socioeconomic disadvantage, young maternal age, maternal hospital admissions for mental health issues, substance misuse and assault. Supplementary analysis for WA showed a time trend with young children (<3 years of age) who entered care spending an increasing proportion of their early years in care. Whilst Manitoba had a larger proportion of children entering care, over time in Western Australia children have been entering care at a younger age and spending more time in care. These latter factors contribute to an increased burden on the out-of-home care system. Manitoba had over five times greater cumulative incidence than WA, however risk factors for entry to out-of-home care were consistent in both countries. Knowledge of the risk factors for entry to out-of-home care can inform targeted support and prevention programs.